Carreiras e circuitos de músicos brasileiros : uma exploração etnográfica no Bairro Alto, Lisboa - Bento, Ricardo; Cordeiro, Graça Índias; Ferro, Lígia (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2016)
Starting from an ethnographic research on the Brazilian popular music world in some of Bairro Alto’s places (Lisbon) this article discuss how the paths pinched by the Brazilian immigrant artists in search of artistic fulfillment and of public recognition are constructed side by side with an intensive sociability between peers, where work and leisure mix together. From the notions of circuit and career, we shall analyze the relationship between paths of spatial mobility and social mobility, as well as the relationship between the constitution of musical scenes in different urban and artistic scales.